2005
DOI: 10.1242/dev.01944
|View full text |Cite
|
Sign up to set email alerts
|

FGF8 is required for cell survival at distinct stages of nephrogenesis and for regulation of gene expression in nascent nephrons

Abstract: During kidney morphogenesis, the formation of nephrons begins when mesenchymal nephron progenitor cells aggregate and transform into epithelial vesicles that elongate and assume an S-shape. Cells in different regions of the S-shaped body subsequently differentiate into the morphologically and functionally distinct segments of the mature nephron. Here, we have used an allelic series of mutations to determine the role of the secreted signaling molecule FGF8 in nephrogenesis. In the absence of FGF8 signaling, nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
227
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(244 citation statements)
references
References 61 publications
16
227
1
Order By: Relevance
“…Studies of several signaling pathways, as well as transcription factors, have revealed genes involved in the patterning the nephron including Fgf8 (Grieshammer et al, 2005), Pou3f3 (Nakai et al, 2003),Sprouty (Basson et al, 2005;Basson et al, 2006), Notch/presenillins (Cheng et al, 2007;Cheng et al, 2003;McCright et al, 2002), and Lhx1 (Kobayashi et al, 2005). In particular, genetic studies have shown several members of the Wnt family of lipidmodified secreted glycoproteins have important roles in the initiation and maintenance of nephron formation and branching morphogenesis Kispert et al, 1998;Majumdar et al, 2003;Stark et al, 1994).…”
Section: Screen For Genes In Nephron Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of several signaling pathways, as well as transcription factors, have revealed genes involved in the patterning the nephron including Fgf8 (Grieshammer et al, 2005), Pou3f3 (Nakai et al, 2003),Sprouty (Basson et al, 2005;Basson et al, 2006), Notch/presenillins (Cheng et al, 2007;Cheng et al, 2003;McCright et al, 2002), and Lhx1 (Kobayashi et al, 2005). In particular, genetic studies have shown several members of the Wnt family of lipidmodified secreted glycoproteins have important roles in the initiation and maintenance of nephron formation and branching morphogenesis Kispert et al, 1998;Majumdar et al, 2003;Stark et al, 1994).…”
Section: Screen For Genes In Nephron Formationmentioning
confidence: 99%
“…Some genes failed to meet the statistical cutoff though they are expressed in E14.5 kidney. These included Fgf8 (Grieshammer et al, 2005), ret (Pachnis et al, 1993;Schuchardt et al, 1994), Pou3f3 (Nakai et al, 2003), Wnt7b (Kispert et al, 1996;Patterson et al, 2001), Ihh (Valentini et al, 1997), and Shh (Yu et al, 2002). Overall, the wildtype profiles had 6824 Present calls (54.9%) and the Wnt4 mutant profiles had 6628 Present calls (53.4%).…”
Section: Transcriptional Profiling Of Wnt4 Mutant Kidneysmentioning
confidence: 99%
“…Furthermore, specification of proximal lineages also requires Lim1/Lhx1 gene function (Kobayashi et al 2005), which may act as an upstream regulator of Notch signaling. Finally, survival of proximal tubular fates is dependent on FGF8 (Grieshammer et al 2005). Far less is known how the more distal nephron segments are specified.…”
mentioning
confidence: 99%
“…The importance of FGF signaling in kidneys has been demonstrated using a transgenic mouse expressing dominant negative FGF receptor (57). The expression of FGF-1 and FGF receptor 1 can be detected in the metanephric mesenchyme during early renal development (58,59), and FGF-1 stimulates ureteric bud branching in organ culture (60). Our study has also identified a number of signaling molecules as WT1 targets, such as IL1RAP, GRB10, SH3-BP5, and other membrane and signaling proteins (supplemental Table S3), that could potentially play important roles to autocrine or paracrine signaling from the ureteric bud for mesenchymal cell survival and differentiation.…”
Section: Discussionmentioning
confidence: 99%